Pelatihan Bahasa Inggris Reading Comprehension “It’s All About Reading Skill” Di SMAN Karya Sakti Muara Kelingi Musi Rawas - Dewi Syafitri; Ani Fiani; Syaprizal Syaprizal (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
SMAN Karya Sakti is one of the educational units at high school level in Karya Sakti, Kec. Muara Kelingi, Kab. Musi Rawas, South Sumatra. In carrying out its activities, SMAN Karya Sakti is under the auspices of the Ministry of Education and Culture with B accreditation. SMAN Karya Sakti is located at Jalan Tapak Libok Blok A, Karya Sakti, Kec. Muara Kelingi, Kab. Musi Rawas, South Sumatra. The aim of this Community Service activity is to provide English language training on reading comprehension which is useful for students in answering ANBK exam questions. The method used in this service is through socialization, incidental training for 1 day. In the process of implementing this activity, the team will provide material as well as tips and tricks on how to easily answer reading skills questions so that it is hoped that students will have adequate abilities in answering questions about reading comprehension both on the ANBK exam and other tests. The expected output target is that students can predict the answers to National Examination questions and answer them correctly and briefly. They also have skills in Reading Skills to analyze the answers to the questions presented